The Paleoanthropology and Archaeology of Big-Game Hunting Protein, Fat, or Politics? - Speth, John D.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
Since its inception, paleoanthropology has been closely wedded to the idea that big-game hunting by our hominin ancestors arose, first and foremost, as a means for acquiring energy and vital nutrients. This assumption has rarely been questioned, and seems intuitively obvious$1 (Bmeat is a nutrient-rich food with the ideal array of amino acids, and big animals provide meat in large, convenient packages. Through new research, the author of this volume provides a strong argument that the primary goals of big-game hunting were actually social and political$1 (Bincreasing hunter$1 (Bs prestige and standing$1 (Band that the nutritional component was just an added bonus. Through a comprehensive, interdisciplinary research approach, the author examines the historical and current perceptions of protein as an important nutrient source, the biological impact of a high-protein diet and the evidence of this in the archaeological record, and provides a compelling reexamination of this long-held conclusion. This volume will be of interest to researchers in Archaeology, Evolutionary Biology, and Paleoanthropology, particularly those studying diet and nutrition.s
How Do We Reconstruct Hunting Patterns in the Past? -- Big-Game Hunting in Human Evolution: The Traditional View -- The Other Side of Protein -- Were Big-Game Hunters Targeting Fat? -- Protein and Pregnancy -- Other Problems with High-Protein Intakes -- Protein and Taste -- Protein and Breast Milk -- Fat in Infancy -- DHA and the Developing Brain -- Big-Game Hunting: Protein, Fat, or Politics?.
Keywords: Social sciences; Nutrition; Evolution (Biology).; Archaeology; Social Sciences; Archaeology; Evolutionary Biology; Nutrition